2021
DOI: 10.5761/atcs.oa.20-00035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of a Customized Mitral Valve Plasty for Functional Mitral Regurgitation with a Low Ejection Fraction and Implications for Preoperative Right Ventricular Function

Abstract: Purpose: To evaluate clinical outcomes of customized mitral valve plasty (MVP) for the treatment of functional mitral regurgitation (FMR) with a low ejection fraction (EF) and to determine which preoperative factors affected the clinical outcome. Methods and Results: MVP was adjusted according to the degree of left ventricle (LV) remodeling. We performed mitral annuloplasty (MAP) alone in 14 patients and added subvalvular procedures (SVPs) in 22 patients at a high risk of recurrent MR. During follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The results reported by Furukawa et al 1) seem to coincide with those reported by Kainuma et al 9) The evidence suggests that the patients with smaller ventricular chambers and improvement of LV remodeling have good results in the long run even with the use of RMA alone because the interpapillary muscle distance (IPMD) is reduced with favorable LV remodeling. Recently, the pivotal role of IPMD has been shown in a report from the Osaka Rosai Hospital.…”
Section: Papillary Muscle Approximationsupporting
confidence: 64%
See 3 more Smart Citations
“…The results reported by Furukawa et al 1) seem to coincide with those reported by Kainuma et al 9) The evidence suggests that the patients with smaller ventricular chambers and improvement of LV remodeling have good results in the long run even with the use of RMA alone because the interpapillary muscle distance (IPMD) is reduced with favorable LV remodeling. Recently, the pivotal role of IPMD has been shown in a report from the Osaka Rosai Hospital.…”
Section: Papillary Muscle Approximationsupporting
confidence: 64%
“…Furukawa et al 1) revealed no difference in a 3-year rate of freedom from cardiac-related mortality when comparing the patients who received RMA alone to those who were managed with the combined RMA and SVR (93% vs 81%; P = 0.3). As highlighted in the results, although one patient who underwent an isolated RMA experienced recurrence of MR ≥2; however, LVDs significantly decreased (from 46 ± 8 to 37 ± 12 mm; P <0.01) and LVEF significantly improved (from 29 ± 7% to 46 ± 18%; P = 0.01).…”
Section: Papillary Muscle Approximationmentioning
confidence: 98%
See 2 more Smart Citations
“…Resistance among surgeons to the use of subvalvular repair (SR) combined with RMA can be explained, at least in part, by the fact that clinical benefit of additional handling the subvalvular apparatus which has been reported in observational studies [6][7][8] has been confirmed in only a few randomized clinical trials [9,10]. Although these randomized studies have shown few rates of mitral regurgitation recurrence and reoperation with the combined procedure using surgery of papillary muscles (PMs), these trials were individually underpowered to detect differences in the frequency of clinical events.…”
Section: Introductionmentioning
confidence: 99%